2021
DOI: 10.21037/qims-20-453
|View full text |Cite
|
Sign up to set email alerts
|

Regional brain changes in patients with diabetic optic neuropathy: a resting-state functional magnetic resonance imaging study

Abstract: Background: To evaluate functional connection density (FCD) in patients with diabetic optic neuropathy (DON) using the resting functional connectivity (FC) method, and to determine the abnormal areas of brain activity.Methods: Patients with DON (n=22; 10 male, 12 female) and healthy controls (HCs; n=22; 10 male, 12 female) were included in the study. The basic characteristics of the groups were matched. Functional magnetic resonance imaging (fMRI) was conducted with participants at rest, and long-and short-ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…We speculated that its abnormal activity may lead to weakening of the ability to regulate rest and work states, and even affect the cerebrum functional connection. Our findings agree with a report by Chen et al [ 34 ]. In this study, they demonstrated abnormal functional connection density in some cerebrum areas of DON patients.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We speculated that its abnormal activity may lead to weakening of the ability to regulate rest and work states, and even affect the cerebrum functional connection. Our findings agree with a report by Chen et al [ 34 ]. In this study, they demonstrated abnormal functional connection density in some cerebrum areas of DON patients.…”
Section: Discussionsupporting
confidence: 94%
“…Alterations of cortical signals can be used to locate cortical functional areas and further study brain functions [ 32 ]. Recently, a lot of rs-fMRI methods were used to observe the brain activities in DON patients, like degree centrality [ 33 ], functional connection density [ 34 ], regional homogeneity [ 35 ] and voxel mirrored homotopic connectivity [ 36 ] methods (details in Table 3 ). This study is the first to use the dALFF method which was ALFF combined with sliding window to reveal the temporal variability of regional intrinsic cerebrum activities in DON patients.…”
Section: Discussionmentioning
confidence: 99%
“…Lower functional connectivity in the ACG and MCG was also observed in patients with schizophrenia [20,21]. Bürger et al [22], whole-brain and a multivariate pattern classification analysis of rs-fMRI were used to study brain activity in patients with emotional disorders. They found significantly decreased ACG activation in patients with the major depressive disorder than in those with bipolar disorder or healthy controls, which potentially indicates impaired bottom-up emotional processing and abnormal automatic emotion regulation.…”
Section: Introductionmentioning
confidence: 99%
“…This data-driven graph theory approach quantifies global and local spontaneous neuronal activity and connectivity of voxels over the whole brain, which leads to faster calculation speeds, more accurate results, and provides complementary information for more targeted analysis (49). Generally, a higher FCD value indicates that there are more functional connections between related areas and other areas (50). It is also regarded as a functional property in hub recognition.…”
Section: Fcd Calculationmentioning
confidence: 99%